2008
DOI: 10.1007/s10198-008-0098-1
|View full text |Cite
|
Sign up to set email alerts
|

Cost effectiveness analysis of heptavalent pneumococcal conjugate vaccine in Germany considering herd immunity effects

Abstract: Based on the health-economic evaluation, the authors recommend the continuation of the general recommendation of PCV7 according to the 3 + 1 schedule within the German Statutory Health Insurance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 47 publications
0
17
0
1
Order By: Relevance
“…However, based on available information, one important difference lies in the assumptions on resource utilization associated with NBPP. The German source applied in the current study [54] reported a relatively low rate, whereas the rate used in the study presented at ACIP appeared to be much higher, as seen in the number of inpatient/outpatient CAP cases avoided and the corresponding assumptions on vaccine effectiveness. Data sources were not detailed.…”
Section: Comparison With Previous Studiesmentioning
confidence: 68%
See 2 more Smart Citations
“…However, based on available information, one important difference lies in the assumptions on resource utilization associated with NBPP. The German source applied in the current study [54] reported a relatively low rate, whereas the rate used in the study presented at ACIP appeared to be much higher, as seen in the number of inpatient/outpatient CAP cases avoided and the corresponding assumptions on vaccine effectiveness. Data sources were not detailed.…”
Section: Comparison With Previous Studiesmentioning
confidence: 68%
“…The price of PPV23 (Pneumovax ® II, single-dose pack; Sanofi Pasteur MSD) was €30.25 and the current unit price of PCV13 (Prevenar 13 ® , single-dose pack; Pfizer, Inc.) was assumed to remain stable following the launch of the vaccine in adults (€65.02) [109]. Costs of administration and treatment of pneumococcal disease were retrieved from German sources [110,111] or updated from previous German studies [54,55] and are detailed in Table 3.…”
Section: Healthcare Resources Used Unit Costs and Pricesmentioning
confidence: 99%
See 1 more Smart Citation
“…For the treatment of hearing loss due to pneumococcal meningitis, the annual costs were estimated from a German cost-effectiveness analysis of cochlear implants in children [70]. The treatment costs of other neurological sequelae were estimated based on the ratio between the costs of treating hearing loss and other neurological sequelae in the study by Claes et al [69]. A copayment of €7 was applied to treatment and vaccine Research Article administration costs based on the assumption that 30% of the patients were fully exempted from a copayment of €10 [115,116].…”
Section: Resource Utilization and Costsmentioning
confidence: 99%
“…The treatment of pneumococcal diseases and vaccine administration costs were obtained from German sources [11,114] and a German cost-effectiveness analysis conducted by Claes et al [69]. For the treatment of hearing loss due to pneumococcal meningitis, the annual costs were estimated from a German cost-effectiveness analysis of cochlear implants in children [70].…”
Section: Resource Utilization and Costsmentioning
confidence: 99%